VINAY AND DARBELNET™S TRANSLATING PROCEDURES USED IN TRANSLATING: ˜THE VILLAGE LEADER™ CHILDREN™S SHORT STORY BY ALYSSON CURRO - SUPATRA, NOFATHANA; PANGESTUTI, TIARA; RAHMAWATI, SELI; LESTARI, NITA (Universitas Negeri Medan, 2024)
This study analyzed the translation procedures used in the translation of the children's short story